2022
DOI: 10.1038/s42255-021-00509-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a regulatory pathway inhibiting adipogenesis via RSPO2

Abstract: Healthy adipose tissue remodeling depends on the balance between de novo adipogenesis from adipogenic progenitor cells and the hypertrophy of adipocytes. De novo adipogenesis has been shown to promote healthy adipose tissue expansion, which confers protection from obesity-associated insulin resistance. Here, we define the role and trajectory of different adipogenic precursor subpopulations and further delineate the mechanism and cellular trajectory of adipogenesis, using single-cell RNA-sequencing datasets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
7
36
0
Order By: Relevance
“…Moreover, it was observed that there is a deficiency of this population under dystrophic conditions which is proportional to increased adipogenesis 55 . However, similar to recent work 48 , we detected more widespread expression of CD142/F3 in our dataset in all populations. If anything, CD142/F3 was slightly higher in our MME + FAPs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, it was observed that there is a deficiency of this population under dystrophic conditions which is proportional to increased adipogenesis 55 . However, similar to recent work 48 , we detected more widespread expression of CD142/F3 in our dataset in all populations. If anything, CD142/F3 was slightly higher in our MME + FAPs.…”
Section: Discussionsupporting
confidence: 92%
“…Cd55 + FAPs from mouse expressed many of the Dpp4 + progenitor marker genes (60/83 of Cd55 + FAP marker genes were Dpp4 + marker genes) such as Dpp4 , Pi16 , Sema3c , Cd55 , and Anxa3 (Figures 3F and S3C). Consistent with this, CD55 was recently used as a marker to sort P1 progenitors in adipose tissue 48 . The marker genes for Icam1 + cells such as Icam1 as well as Pparg , Cd36 , and Fabp4 , all of which are considered pre-adipogenic markers, were not expressed in Gpc3 + and Mme + FAPs, (Figure S3C).…”
Section: Resultsmentioning
confidence: 71%
“…This clustering resolved three distinct ASC cell types prominent in iBAT controls: ASC1-3 (Figure 2C, left). Genes that define these clusters were similar to the expression profiles of mouse PDGFRA+ ASC subtypes recently identified in various mouse fat depots (Burl et al 2018;Dong et al 2022;Hepler et al 2018;Merrick et al 2019;Rondini and Granneman 2020;Schwalie et al 2018). In control mice, ASC subtypes were distinguished by genes that encode extracellular matrix (ECM) and matrix remodeling proteins, and paracrine signaling proteins of the transforming growth factor beta superfamily.…”
supporting
confidence: 63%
“…Most recently, Dong et al. ( 60 ) described RSPO2/LGR4 as critical regulators of progenitor cell differentiation towards adipocytes. In mice, elevated plasma RSPO2 levels were additionally associated with insulin resistance, also plasma RSPO2 levels in humans (specifically in men only) correlated with insulin resistance and fat distribution (elevated RSPO2 levels were associated with obesity).…”
Section: Lgr4 and Regulation Of Metabolism In Health And Diseasementioning
confidence: 99%